2021
DOI: 10.5114/fmpcr.2021.108200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic prescriptions for sepsis in the Neonatal Intensive Care Unit in a Tertiary Hospital in North Sumatera, Indonesia

Abstract: Background. Neonatal sepsis is a leading cause of morbidity and mortality worldwide. The evaluation of antibiotic prescription in neonatal intensive care units (NICUs) is important for reducing inappropriate antibiotic use and minimizing the development of antibiotic resistance. Antimicrobial stewardship programs potentially promote a prudent use of antibiotics; however, the approach in NICUs is not yet optimal. Objectives. The aim of our study was to evaluate antibiotic prescriptions for neonatal sepsis in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Such drugs should thus be withdrawn as soon as possible, and their administration should be immediately discontinued if it is found that they were introduced into the treatment without proper indication [71], especially when there is a dominance of viral infections [72]. on the other hand, justified antibiotic treatment must also not be discontinued too early [73].…”
Section: Resultsmentioning
confidence: 99%
“…Such drugs should thus be withdrawn as soon as possible, and their administration should be immediately discontinued if it is found that they were introduced into the treatment without proper indication [71], especially when there is a dominance of viral infections [72]. on the other hand, justified antibiotic treatment must also not be discontinued too early [73].…”
Section: Resultsmentioning
confidence: 99%
“…Microbial resistance to antimicrobials has become a global problem, with various detrimental impacts that can reduce the quality of health services. The emergence and development of resistant microbes occurs due to selection pressures associated with the use of antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%